Stylistics of Lexical and Grammatical Meaning in the Poem "Al-I’tiraf" - Ramadani, Ermi Anisa; Marwah, Assania Sofatul; Azizah, Alifia Ni’mahtul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Stylistics, or language style, is a method used by writers to convey ideas in accordance with their intended purpose and the impact they wish to achieve. In literary creation, these effects serve to deepen meaning, illustrate objects and events with imagination, and evoke specific emotional responses in the reader. The tools used to convey such ideas and effects are not limited to linguistic symbols but also include various semiotic systems capable of expressing ideas with a range of potential aesthetic impacts. Poetry, or shi’ir, is considered a beautiful literary form due to the author’s choice of diction. Shi’ir has existed since Roman and Arab civilizations, and Arabic poetry remains a vibrant oral tradition today. One influential Arabic literary work in Indonesia is the poetry of Abu Nuwas, especially his poem "Al-I’tiraf". This poem is believed to be a collection of verses written by Abu Nuwas before his death. The aim of this study is to apply lexical and grammatical meaning analysis to the diction used in Abu Nuwas’ poem Al-I’tiraf, as well as to identify the classification of words with lexical and grammatical meanings. The study also seeks to examine and analyze the stylistic aspects of lexical and grammatical meanings within the poem. A descriptive and qualitative approach is used, collecting data through repeated reading, note-taking, and data categorization. The theoretical framework employed is based on lexical and grammatical semantics. This poem was chosen due to its popularity in Indonesian Islamic boarding schools (pesantren), where it holds profound meaning for its readers. However, questions remain as to whether the poem was truly authored by Abu Nuwas. Therefore, a deeper investigation into the language style and semantic analysis—both lexical and grammatical—of this poem is necessary.